Log Linear Model on Contingency Table to Analyze Relationship between Age, Income, and Health Insurance Ownership - Evelyn Priscilla; Jeslyn Prinssesa; Mei Siang Jemima Aurelia; Edwin Setiawan Nugraha (Journal of Actuarial, Finance, and Risk Management, 2022)
Health insurance is a type of insurance that is important for everyone to have since it has benefits as protection against health risks that may occur in the future. Unfortunately, most people nowadays do not really want health insurance, especially people who are relatively young and have low incomes. Young people feel that they are still strong and do not get sick easily, while people with low incomes cannot afford to buy insurance because of the high premium prices. Therefore, the relationship between age, income, and insurance ownership (other than BPJS) needs to be known to help insurance companies develop new strategies. In this study, we implemented a Log-Linear model on a contingency table using survey data that we took in Jabodetabek, Bali, and Kalimantan areas. The results showed that the Log-Linear model (OI.OA.IA) was efficient enough to determine the relationship between age, income, and insurance ownership with a 95% confidence level. Homogeneous interactions happened so that there is no relationship between age, income, and insurance ownership, but there were relationships between age and income, age and insurance ownership, and income and insurance ownership. This research is expected to assist insurance companies in determining their target market and developing their marketing.